A kind of high specific strength porous mullite ceramic and preparation method thereof

By using a ball mill wet mixing and sintering treatment in the preparation of porous mullite ceramics, the problems of low mechanical strength and complex process of ceramics are solved, and porous mullite ceramics with high specific strength and high porosity are achieved, which simplifies the process and reduces the The cost.

CN116535231BActive Publication Date: 2025-01-03SOUTH CHINA UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310388192.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-12
Publication Date
2025-01-03
Estimated Expiration
2043-04-12

AI Technical Summary

Technical Problem

The existing porous mullite ceramics have low mechanical strength and complex preparation processes, which limit their application range.

Method used

The raw materials are wet-mixed by a ball mill, and a cosolvent, whisker catalyst and pore-forming agent are added. After drying, grinding, sieving, pressing, and then sintering in a high-temperature furnace to prepare high-specific strength porous mullite ceramics.

Benefits of technology

Porous mullite ceramics with high porosity, low density and high mechanical strength are obtained. The process is simple, suitable for large-scale production, and have a wider range of applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116535231B_ABST
    Figure CN116535231B_ABST
Patent Text Reader

Abstract

The invention discloses a high specific strength porous mullite ceramic and a preparation method thereof. The method comprises: wet mixing alumina, silicon dioxide, a cosolvent, a whisker catalyst, and a pore-forming agent in a ball mill to obtain a wet material, drying, grinding, and sieving the wet material to obtain a mixed dry powder; adding a binder to the mixed dry powder, grinding and mixing evenly, sieving, pressing and forming, and drying to obtain a ceramic green body, which is placed in a high-temperature furnace for sintering to obtain the high specific strength porous mullite ceramic. The strength of the porous ceramic of the invention is ensured by a method of in-situ growth of whiskers for toughening. The use of a whisker catalyst can promote the growth of secondary mullite whiskers and inhibit the densification of the ceramic matrix. While increasing the porosity of the ceramic, its strength is ensured not to be reduced, thereby obtaining a high specific strength porous mullite ceramic with a higher porosity and flexural strength. The method is simple in process, easy to operate, and suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic materials, and in particular to a high specific strength porous mullite ceramic and a preparation method thereof. Background Art

[0002] Porous mullite ceramics are widely used in environmental management, bioengineering, high temperature insulation materials, catalyst carriers, aerospace structural materials and other fields due to their high porosity, high specific surface area and good stability, such as water-oil separation filtration membranes, sound-absorbing materials, industrial furnace insulation materials, artificial bionic bone joints, etc. However, due to its pore structure, its mechanical strength is generally low. Therefore, the porous mullite ceramics are strengthened by whiskers to obtain high specific strength porous mullite ceramics with low density and high strength, which can broaden the application field of porous mullite ceramics.

[0003] Whiskers are high-purity, fine single crystals that grow catalytically under controlled conditions, and needle-shaped mullite whiskers are whiskers with an aspect ratio of more than 10. There are almost no crystal structure defects such as grain boundaries, dislocations, and vacancies in their structure. Therefore, they have excellent mechanical and physical properties and can act as a reinforcement in the internal structure of porous mullite ceramics, significantly improving the mechanical properties of the material. Whisker-toughened ceramics achieve the purpose of strengthening and toughening ceramic materials by causing crack bridging, deflection, whisker pullout, and other phenomena during crack expansion, forming an energy consumption mechanism.

[0004] CN114988903 discloses a high-strength, low-shrinkage porous ceramic and its preparation method, which uses silicon carbide, aluminum hydroxide, yeast powder and graphite as raw materials, and after mixing and molding, the porous ceramic green body is sintered at a rate of 5°C / min and a sintering temperature of 1325°C, and is kept at 325°C, 500°C, 900°C and 1325°C for one hour respectively, and then cooled with the furnace to obtain the porous ceramic. The prepared porous ceramic has a porosity of 55.7% and a bending strength of 15.96MPa. The narrow pore size distribution and regular pore structure of the porous ceramic are conducive to improving its strength, but its mechanical strength is still not high enough, and the preparation process is relatively complicated, which limits its application range. Summary of the invention

[0005] In order to overcome the shortcomings and deficiencies of the prior art, the object of the present invention is to provide a high specific strength porous mullite ceramic and a preparation method thereof. The porous mullite ceramic obtained by the method of the present invention has the advantages of high porosity, low density, high mechanical strength, and simple process, and can be widely used.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0008] (1) wet-mixing the raw materials in a ball mill to obtain a wet material, drying, grinding, and sieving the wet material to obtain a mixed dry powder, wherein the raw materials are composed of the following components in parts by weight: 40-60 parts of aluminum oxide, 25-45 parts of silicon dioxide, 5-25 parts of a solvent, 2-8 parts of a whisker catalyst, and 0-25 parts of a pore-forming agent;

[0009] (2) Adding 0.5-10 parts by weight of a binder to the mixed dry powder in step (1), grinding and mixing the mixture evenly, sieving, pressing and molding, and drying to obtain a ceramic green body, which is then sintered in a high-temperature furnace to obtain the high specific strength porous mullite ceramic.

[0010] Preferably, the co-solvent in step (1) is one or more of magnesium oxide and sodium silicate.

[0011] Preferably, the whisker catalyst in step (1) is one or more of boron oxide and aluminum fluoride.

[0012] Preferably, the pore-forming agent in step (1) is corn starch.

[0013] Preferably, the wet mixing speed in step (1) is 300-600 r / min and the mixing time is 0.5-3 h.

[0014] Preferably, in step (1), 100-300 parts by weight of deionized water are added during the wet mixing.

[0015] Preferably, the mesh size of the sieve used for screening in step (1) and step (2) is 100-300 mesh.

[0016] Preferably, the drying temperature in step (1) and step (2) is 80-110° C., and the drying time is 12-24 hours.

[0017] Preferably, the adhesive in step (2) is a PVA adhesive.

[0018] Further preferably, the PVA adhesive is a PVA solution with a mass concentration of 1-10%. More preferably, the PVA adhesive is a PVA solution with a mass concentration of 5%.

[0019] Preferably, the pressure of the compression molding in step (2) is 30-60MPa, and the holding time is 1-5min.

[0020] Preferably, the sintering temperature in step (2) is 1200-1500° C., the sintering time is 2-6 hours, and the heating rate is 1-10° C. / min.

[0021] Further preferably, the temperature of the sintering treatment in step (2) is 1300-1500°C.

[0022] The beneficial effects of the present invention are as follows:

[0023] (1) The present invention adopts a pore-forming agent addition method to prepare porous mullite ceramics, thereby preparing porous mullite ceramics with relatively high porosity.

[0024] (2) The present invention provides a high-specific-strength porous mullite ceramic and a method for preparing the same, which can in-situ grow mullite whiskers with a high aspect ratio, reduce the degree of matrix densification, increase the porosity of the porous ceramic, and improve its mechanical properties through mechanisms such as crack bridging, crack deflection, and whisker extraction.

[0025] (3) The preparation method and process of the present invention are simple, can reduce energy consumption, shorten preparation time, reduce costs, and are suitable for mass production. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is a specific preparation flow chart of the present invention.

[0027] Figure 2 The cross section of the high specific strength porous mullite ceramic of Example 1 (left) and its microstructure after etching (middle and right). DETAILED DESCRIPTION

[0028] In order to make the purpose and advantages of the present invention more concise and clear, the present invention will be illustrated by the following specific examples, but the present invention is by no means limited to these examples. The following examples are only preferred embodiments of the present invention and are only used to illustrate the present invention and cannot be understood as limiting the scope of the present invention. It should be pointed out that any modifications, equivalent substitutions and improvements made within the essence and principles of the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the attached claims.

[0029] Example 1

[0030] A method for preparing high specific strength porous mullite ceramics, the preparation flow chart is as follows Figure 1 As shown, the following steps are included:

[0031] (1) Mixing: 50 g of alumina powder, 35 g of silica powder, 10 g of sodium silicate, 5 g of aluminum fluoride, 15 g of corn starch, and 2 g of boron oxide were placed in a ball mill and milled at 300 r / min for 2 h using deionized water (117 g) as a dispersant. The mixture was dried and ground, and passed through a 100-mesh sieve. Then, 2 g of a 5% PVA solution was added, the mixture was thoroughly mixed by grinding, and the mixture was passed through a 100-mesh sieve again to obtain a mixed powder.

[0032] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0033] (3) Sintering: The porous mullite ceramic green body is sintered at a rate of 3°C / min and a temperature of 1400°C for 2 hours, and then cooled in the furnace to obtain porous mullite ceramics.

[0034] like Figure 2 As shown, there are a large number of interconnected pores inside the prepared porous mullite ceramic, with a porosity of 42.26%. Mullite whiskers grow in the pores, and a large number of rod-shaped secondary mullite grains are embedded in the glass phase. Some rod-shaped grains grow through the pores to form an interlocking structure. These interlocked mullite whiskers can increase the energy required for ceramic fracture by bridging cracks and pulling out the bonded mullite whiskers, thereby obtaining a porous mullite ceramic sample A.

[0035] Example 2

[0036] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0037] (1) Mixing: 50 g of alumina powder, 35 g of silicon dioxide powder, 10 g of sodium silicate, 5 g of aluminum fluoride, and 15 g of corn starch were placed in a ball mill with deionized water (115 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0038] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0039] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1400°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample B.

[0040] Example 3

[0041] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0042] (1) Mixing: 50 g of alumina powder, 35 g of silica powder, 10 g of sodium silicate, 5 g of aluminum fluoride, and 20 g of corn starch were placed in a ball mill with deionized water (120 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0043] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0044] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1400°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample C.

[0045] Comparative Example 1

[0046] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0047] (1) Mixing: 50 g of alumina powder, 35 g of silicon dioxide powder, 10 g of sodium silicate, 5 g of aluminum fluoride, and 25 g of corn starch were placed in a ball mill with deionized water (125 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0048] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0049] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1400°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample D.

[0050] Comparative Example 2

[0051] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0052] (1) Mixing: 65 g of alumina powder, 20 g of silicon dioxide powder, 10 g of sodium silicate, and 5 g of magnesium oxide were placed in a ball mill with deionized water (100 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0053] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0054] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1400°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample E.

[0055] Comparative Example 3

[0056] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0057] (1) Mixing: 50 g of alumina powder, 35 g of silica powder, 10 g of sodium silicate, and 5 g of magnesium oxide were placed in a ball mill with deionized water (100 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and then 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0058] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0059] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1400°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample F.

[0060] Comparative Example 4

[0061] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0062] (1) Mixing: 50 g of alumina powder, 35 g of silicon dioxide powder, 10 g of sodium silicate, and 5 g of aluminum fluoride were placed in a ball mill with deionized water (100 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and then 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0063] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0064] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1300°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample G.

[0065] Comparative Example 5

[0066] A method for preparing high specific strength porous mullite ceramics comprises the following steps:

[0067] (1) Mixing: 65 g of alumina powder, 20 g of silicon dioxide powder, 10 g of sodium silicate, and 5 g of aluminum fluoride were placed in a ball mill with deionized water (100 g) as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, the mixture was passed through a 100-mesh sieve, and then 2 g of a 5% PVA solution was added. The mixture was fully mixed by grinding and passed through a 100-mesh sieve again to obtain a mixed powder.

[0068] (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body;

[0069] (3) Sintering: The porous mullite ceramic green body was sintered at a rate of 3°C / min and a temperature of 1300°C for 2 h, and then cooled in the furnace to obtain a porous mullite ceramic sample H.

[0070] The porous mullite ceramics of Examples 1 to 3 and Comparative Examples 1 to 5 were tested for performance, and the test results are shown in the following table:

[0071] Table 1 Sample performance test results

[0072]

[0073] Note:

[0074] Porosity and density: The sample size is a disc with a diameter of 20 mm and a thickness of 5 mm. The Archimedean drainage method is used for testing. At least five samples of each type are tested and the average value is taken.

[0075] Flexural strength: measured by SUST universal testing machine produced by Zhuhai Sansi Taijie Electronic Equipment Co., Ltd., using three-point bending method, span of 30mm, sample size of 3mm*4mm*35mm, pressure rate of 0.5mm / min, at least five samples of each type, tested the flexural strength separately and took the average value;

[0076] Specific strength: at least five samples of each type are tested for flexural strength and density respectively. The ratio of flexural strength to density of each sample is calculated as the specific strength of the sample. The average value of the five samples is taken.

[0077] from Figure 2From the microstructure photos of porous mullite ceramics, it can be found that the porous mullite ceramics prepared by this method are composed of an amorphous phase and overlapping mullite whiskers, forming a high-strength three-dimensional network structure. At the same time, the abnormal grain growth of mullite grains hinders the densification of the ceramics. Therefore, under this mechanism, a high-specific-strength porous mullite ceramic with high porosity and high flexural strength is formed.

[0078] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some modifications and changes to the invention should also fall within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the invention.

Claims

1. A method for preparing high specific strength porous mullite ceramics, characterized in that: The steps include: (1) Mixing: 50 g of alumina powder, 35 g of silica powder, 10 g of sodium silicate, 5 g of aluminum fluoride, 15 g of corn starch, and 2 g of boron oxide were placed in a ball mill with 117 g of deionized water as a dispersant and ball milled at 300 r / min for 2 h. After drying and grinding, sieve through a 100-mesh screen, 2 g of a 5% PVA solution was added, the mixture was thoroughly mixed by grinding, and sieved through a 100-mesh screen again to obtain a mixed powder. (2) Molding: The mixed powder is placed in a molding mold, dry-pressed at a pressure of 47 MPa, maintained at the pressure for 2 min, and then placed in a drying oven at 80° C. for 24 h to obtain a porous mullite ceramic green body; (3) Sintering: The porous mullite ceramic green body is sintered at a rate of 3°C / min and a temperature of 1400°C for 2 hours, and then cooled in the furnace to obtain porous mullite ceramics.

2. A porous mullite ceramic with high specific strength prepared by the preparation method according to claim 1.